Microwave-assisted Deep Eutectic Solvent Pretreatment of Salix babylonica for High-Purity and Antioxidative Lignin Production - Yinglong Wu; Zhong Wu; Wei Wang; Yanfang Tai; Yanwen Chen; Yan Wang; Yu Liu (BioResources)
Two kinds of deep eutectic solvents (DES) were synthetized and utilized microwave-assisted technology to rapidly disrupt the recalcitrance of lignocellulosic biomass, thereby further enhancing the yield of lignin and obtaining lignin with high-purity and notable antioxidant properties. The DES system, synthetized with choline chloride/formic acid and choline chloride/tartaric acid in a molar ratio of 1:6, was carried out at 140 °C for efficient lignocellulosic biomass separation. Surprisingly, the application of microwave-assisted DES for extracting lignin from Salix babylonica wood was able to substantially shorten the conventional 12 h extraction process to 30 min while significantly improving the separation efficiency. Especially for the DES system synthetized with choline chloride and formic acid, after pretreatment for 30 min, the lignin yield was 70.8%. The lignin fractions had high purity (>88%) and low molecular weight (Mw 1756 to 2546 g/mol). Infrared spectroscopy and two-dimensional nuclear magnetic resonance revealed that the recovered lignin components retained intact aromatic structures, which showed typical structure of G/S-type. Furthermore, the DES lignin fractions exhibited excellent antioxidant properties compared with butyl hydroxyanisole (BHA), thereby laying a foundation for the value-added utilization of lignin.